Biological effects of exosomes derived from 2D and 3D culture adipose stem cells on JEC Cell proliferation and migration - Li, Yifen; Wang, Gangwei; Zhang, Yi; Xu, Tao; Jiang, Xuefeng (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo explore the biological impacts of exosomes derived from adipose stem cells cultured under two-dimensional (2D) and three-dimensional (3D) conditions on endometrial adenocarcinoma cells (JEC cells).Materials and methodsExosomes were isolated and extracted from adipose stem cells grown in 2D and 3D cultures. JEC cells were allocated into three categories: a control group, a 2D group, and a 3D group. Cultivation of JEC cells occurred with distinct media (supplemented with or without 2D/3D adipose-derived stem cell exosomes) per group. Endometrial cancer cell viability was evaluated by a Cell Counting Kit-8 (CCK-8) assay. Scratch assays gauged the migratory behavior of endometrial adenocarcinoma cells. A Transwell assay quantified cellular invasiveness.ResultsThe 3D group exhibited amplified cell proliferation (p < 0.05). Higher wound closure rates at 72 h were observed in the 3D group (p < 0.05). The Transwell assay demonstrated a substantial rise in the number of JEC cells traversing the Transwell chamber within the 3D group at 48 h (p < 0.05).ConclusionExosomes obtained from 2D and 3D adipose stem cells significantly bolstered cell proliferation, invasion, and migration. Exosomes sourced from 3D adipose-derived stem cells displayed greater efficacy than their 2D counterparts.